Ethnopharmacology in Treatment of Hypertension from Yala Provinces, Thailand - Hookheaw, Suthinee; Neamsuvan, Oratai (Science Essence Journal, 2020)
บทคัดย่อ การศึกษานี้มีวัตถุประสงค์เพื่อสำรวจภูมิปัญญาการรักษาโรคและรวบรวมพืชสมุนไพรที่ใช้รักษาโรคความดันโลหิตสูงของหมอพื้นบ้านในจังหวัดยะลา ด้วยการสำรวจภาคสนามและสัมภาษณ์แบบกึ่งโครงสร้างกับหมอพื้นบ้านที่คัดเลือกแบบจำเพาะเจาะจง จำนวน 8 คน เพื่อรวบรวมข้อมูลเกี่ยวกับทฤษฎีการเกิดโรค หลักการรักษา ชนิดพืช ส่วนที่ใช้และวิธีการเตรียม จากนั้นวิเคราะห์ข้อมูลโดยใช้สถิติเชิงพรรณนาและหาค่าการใช้ประโยชน์สูงสุดของสมุนไพรแต่ละชนิด (Use value, UV) ผลการศึกษาพบว่า หมอพื้นบ้านส่วนใหญ่เชื่อว่าโรคความดันโลหิตสูงเกิดจากความผิดปกติของธาตุลมและธาตุไฟในร่างกาย สมุนไพรที่ใช้มักมีสรรพคุณขับลมและปรับไฟธาตุ พบพืชสมุนไพรที่ใช้รักษาโรคความดันโลหิตสูงจำนวน 35 ชนิด (30 สกุลและ 21 วงศ์) นอกจากนี้พบว่า 1) วงศ์ที่พบมากที่สุด ได้แก่ Zingiberaceae (12.50%) 2) วิธีการเตรียมยาที่นิยมใช้มากที่สุดคือการต้ม (57.14%) และ 3) ส่วนของพืชที่ใช้บ่อยที่สุดคือใบ (31.43%) โดยบอระเพ็ด หรือ Tinospora crispa มีค่า UV สูงสุด (0.375) ตามด้วยหญ้าใต้ใบ หรือ Phyllanthus urinaria (0.25) ทั้งนี้มีพืชสมุนไพร 11 ชนิด ยังไม่มีรายงานเกี่ยวกับฤทธิ์ลดความดันโลหิตสูง ดังนั้นเพื่อสนับสนุนประสิทธิภาพของพืชสมุนไพรกลุ่มดังกล่าวควรมีการศึกษาฤทธิ์ลดความดันโลหิตสูงเพิ่มเติม ABSTRACT This study aimed to survey the wisdom of disease treatments and to collect medicinal plants used to treat hypertension of folk healers in Yala province. Field survey and semi-structured interviews were conducted with 8 folk healers who were chosen purposively. The data gathered were included the theories of disease, principles of treatment, plant species, parts used and methods of preparation. The documented data were analysed by descriptive statistics and use value (UV) index. From the results, the most healers believed that hypertension was caused by disorder of wind and fire elements in the body. Therefore, medicinal plants used tentatively have the properties to expel wind and adjust fire elements. A total of 35 plant species (30 genera and 21 families) were used for hypertension treatment. In addition, found that 1) the most frequently families was Zingiberaceae (12.50%) 2) the major mode of preparation was decoction (57.14%) and 3) the most frequently used part was leaves (31.43%). Tinospora crispa had the highest UV (0.375), followed by Phyllanthus urinaria (0.25). Ten species have not been reported in antihypertension activity, therefore, they should be further studied to support herbal activity.